2009
DOI: 10.1371/journal.pgen.1000430
|View full text |Cite
|
Sign up to set email alerts
|

A Plant Germline-Specific Integrator of Sperm Specification and Cell Cycle Progression

Abstract: The unique double fertilisation mechanism in flowering plants depends upon a pair of functional sperm cells. During male gametogenesis, each haploid microspore undergoes an asymmetric division to produce a large, non-germline vegetative cell and a single germ cell that divides once to produce the sperm cell pair. Despite the importance of sperm cells in plant reproduction, relatively little is known about the molecular mechanisms controlling germ cell proliferation and specification. Here, we investigate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
209
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(222 citation statements)
references
References 36 publications
12
209
1
Order By: Relevance
“…AtMYB125/ DUO1 is a pollen-specific factor controlling male germ cell division and differentiation (Brownfield et al 2009). AtMYB33 and AtMYB65 redundantly facilitate both anther and pollen development (Millar and Gubler 2005).…”
Section: Role In Plant Developmentmentioning
confidence: 99%
“…AtMYB125/ DUO1 is a pollen-specific factor controlling male germ cell division and differentiation (Brownfield et al 2009). AtMYB33 and AtMYB65 redundantly facilitate both anther and pollen development (Millar and Gubler 2005).…”
Section: Role In Plant Developmentmentioning
confidence: 99%
“…5 The R2R3 MYB transcription factor DUO1 and a nuclear protein DUO3 control proliferation of male germ line. 6,7 Analysis of lbd27 mutant indicated that LBD27 plays a role in the correct timing and orientation of the asymmetric microspore division. 8 Several LBD gene family members have been shown to play important roles in diverse aspects of lateral organ development in Arabidopsis, rice and maize.…”
mentioning
confidence: 99%
“…This year two papers reported a role of two members of this Arabidopsis subfamily in the regulation of the cell cycle. These are AtMYB59, which is involved in root growth [8] and DUO1 (AtMYB125), encoding a male germline-specific protein [9].…”
mentioning
confidence: 99%
“…In another recent paper Brownfield et al showed that the Arabidopsis male germline-specific DUO1 gene, is required for correct male germline differentiation and for male germline cell division, controlling the expression of the G2/M regulator CYCB1;1 [9]. Expression of the cyclin B as a chimeric gene under the control of the DUO1 promoter can partially rescue defective germ cell division in the duo1 mutant.…”
mentioning
confidence: 99%
See 1 more Smart Citation